2022
DOI: 10.3390/biology11081149
|View full text |Cite
|
Sign up to set email alerts
|

CRP Involved in Nile Tilapia (Oreochromis niloticus) against Bacterial Infection

Abstract: C-reactive protein (CRP) is an acute-phase protein that can be used as an early diagnostic marker for inflammation, which is also an evolutionarily conserved protein and has been identified from arthropods to mammals. However, the roles of CRP during the immune response of Nile tilapia (Oreochromis niloticus) remain unclear. In this study, a CRP gene from Nile tilapia (On-CRP) was identified, and its roles in response to bacterial infection were investigated in vivo or in vitro. On-CRP was found to contain an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Results also indicated that about 50% of treatments reported similar creatinine levels to the control group (0.19 mg/dL). It is interesting that C-reactive protein (CRP) was <0.6 for all treatments, and was lower than the serum CRP level of normal O. niloticus (2.51 mg/L) as Julinta et al (2019) reported, indicating that no inflammation occurred in all of the studied fish, where Li et al (2022) reported that Creactive protein is an acute-phase protein that can be used as an early diagnostic marker for inflammation. In addition, direct bilirubin was not detected, with minimal values for total bilirubin.…”
mentioning
confidence: 86%
“…Results also indicated that about 50% of treatments reported similar creatinine levels to the control group (0.19 mg/dL). It is interesting that C-reactive protein (CRP) was <0.6 for all treatments, and was lower than the serum CRP level of normal O. niloticus (2.51 mg/L) as Julinta et al (2019) reported, indicating that no inflammation occurred in all of the studied fish, where Li et al (2022) reported that Creactive protein is an acute-phase protein that can be used as an early diagnostic marker for inflammation. In addition, direct bilirubin was not detected, with minimal values for total bilirubin.…”
mentioning
confidence: 86%
“…Numerous studies have shown that both IL‐1β and IL‐18 are expressed in human atheroma and exhibit an adverse effect on cardio‐cerebrovascular diseases by causing local inflammation, elevating adhesion molecule expression and boosting procoagulant activity (Y. Jin et al, 2022). The production of IL‐1β and IL‐18 results in elevations of IL‐6 and C‐reactive protein (CRP) (Calabrese & Rose‐John, 2014; Q. Li et al, 2022). IL‐6 and C‐reactive protein are mediators of inflammation.…”
Section: The Main Biological Functions Of the Aim2 Inflammasomementioning
confidence: 99%
“…IL‐6 and C‐reactive protein are mediators of inflammation. In an atherosclerosis‐prone model, alterations in the levels of IL‐1β and IL‐18 are associated with changes in the expression of the AIM2 inflammasome and atherosclerosis (Calabrese & Rose‐John, 2014; Q. Li et al, 2022). Consistently, IL‐1β induced by overexpression of AIM2 worsened AAA, while AIM2 deficiency alleviated that phenomenon (X. Wu et al, 2016).…”
Section: The Main Biological Functions Of the Aim2 Inflammasomementioning
confidence: 99%
“…CRP has been observed in animals other than humans, including the freshwater fish Channa punctatus ( 9 ) and the Nile tilapia Oreochromis niloticus ( 10 ). Based on amino acid sequence analysis and the number of subunits, the main structure of human and rabbit CRP has been identified.…”
Section: Phylogenetic History Of Crpmentioning
confidence: 99%
“…Nile tilapia’s CRP gene has also been discovered ( 10 ). The data clearly demonstrate that CRP in Nile tilapia is a robust and active participant in the anti-bacterial immune response beginning with the agglutination of bacteria as well as the regulation of phagocytosis and inflammation.…”
Section: Fish Crpmentioning
confidence: 99%